The Effect of Work Environment on Organizational Culture and Employees Performance - Antoneta C Yoghan; Abdul Rahman Laba; Andi Aswan; Bintang Balele (Hasanuddin Journal of Business Strategy, 2020)
Employee performance is a main concern for public organizations to provide excellent service to public communities. To reach a high employee performance, human resources is prominent key successes. This study aims to analyse the effect of work environment on organizational culture and employee performance mediated by organizational culture at Regional Secretariat Office of the Boven Digoel Distrct. The study applied Structural Equation Modeling (SEM) with the use of a saturated sample from sevent working divisions at Secretariat Office. With respect to analysis, all weighted loading factor indicate above 0.50 and coefficient path paramaters for the relationship between the work environment and organizational culture and employee peformance are a positive and significant. This is also valid for the relationship between organizational culture and employee performance.